Risk‐Reducing Strategies for Ovarian Cancer in BRCA Mutation Carriers: A Balancing Act. (17th March 2017) - Tschernichovsky, Roi; Goodman, Annekathryn
Abstract : Objective: The objective of this study was to review the role of bilateral salpingo‐oophorectomy in BRCA mutation (m BRCA ) carriers and alternative interventions in risk reduction of ovarian cancer (OC). Materials and Methods: A systematic review using PubMed, MEDLINE, EMBASE, and the Cochrane library was conducted to identify studies of different strategies to prevent OC in m BRCA carriers, including bilateral salpingo‐oophorectomy, prophylactic salpingectomy with delayed oophorectomy, intensive surveillance, and chemoprevention. Results: Risk‐reducing bilateral salpingo‐oophorectomy is an effective intervention, but its associated morbidity is substantial and seems to curtail uptake rates among the target population. Although there is much interest and a strong theoretical basis for salpingectomy with delayed oophorectomy, data on its clinical application are scarce with regard to screening, the use of an algorithmic protocol has recently shown favorable albeit indefinite results in average‐risk postmenopausal women. Its incorporation into studies focused on high‐risk women might help solidify a future role for screening as a bridge to surgery. The use of oral contraceptives for chemoprevention is well supported by epidemiologic studies. However, there is a lack of evidence for advocating any of the other agents proposed for this purpose, including nonsteroidal anti‐inflammatory drugs, vitamin D, and retinoids. Conclusion: Further studies are needed before salpingectomy with delayed oophorectomy or intensive surveillance can be offered as acceptable, less morbid alternatives to upfront oophorectomy for m BRCA carriers. Abstract : The role of bilateral salpingo‐oophorectomy in BRCA mutation carriers and alternative interventions in risk reduction of ovarian cancer is reviewed. The efficacy and pitfalls of risk‐reducing bilateral salpingo‐oophorectomy are summarized, as well as its effect on quality of life and alternative preventative strategies.